Hematological and biochemical reference intervals for Bothrops asper and Crotalus simus (Serpentes: Viperidae), maintained in captivity for venom extraction. (May 2016) - Gómez, Aarón; Arroyo, Cynthia; Astorga, Wilson; Chacón, Danilo; Rodríguez, Santos; Jiménez, Manuel
Abstract This study presents hematological and biochemical reference intervals (RIs) for two species of viper snakes (Bothrops asper andCrotalus simus ), which are the first of their type particularly for these two species maintained in captivity and for extraction of venom purposes. A total of 77 snakes were used in developing the study; specifically 39B. asper and 38C. simus snakes. Blood samples were obtained by puncturing the caudal vein, and hematological tests were performed manually by two independent technicians. Plasma biochemistry parameters were determined by an automatized analyzer. There are hematological differences between wild-caught and captiveB. asper in the percentage of heterophils (P < 0.001), while in captive and wild-caughtC. simus, the differences are found in the percentage of eosinophils, lymphocytes, and monocytes (P < 0.001). Differences in glucose (P = 0.012), uric acid (P < 0.001), and cholinesterase (P = 0.004) are found in captive and wild-caughtB. asper . Differences in albumin (P = 0.002), calcium (P < 0.001), CK (P = 0.04), and LDH (P = 0.037) are found between captive and wild-caughtC. simus . This study constitutes the first set of hematological and biochemical RIs forB. asper andC. simus maintained in captivity with the purpose of producing antivenom in Costa Rica. The establishment of comprehensive RIs for hematology and plasma biochemistry for these two species of snakes is useful for interpretation of blood test results, moreover, to serving as a reference for viper snakes used for research purposes.